In Silico Design Of Phenyl Acetamide Derivatives As Parp1 Inhibitors Targeting Brca1/2-Mutated Breast And Ovarian Cancers. - Meena, Ganesh; .Venkatheshan, N; Baqi, Mohd Abdul; Muthukumaran, M.; Jayanthi , Koppula (Journal of Neonatal Surgery, 2025)
Objective: In this work, a number of new phenyl acetamide derivative compounds were designed and evaluated for their possible inhibitory effect against poly (ADP-Ribose) polymerase 1 (PARP1), a crucial enzyme linked to ovarian and breast malignancies with BRCA1/2 mutations. The goal was to compare these compounds with standard drugs Olaparib and Niraparib. Methods: Molecular docking and MM-GBSA (Molecular Mechanics/Generalized Born Surface Area) calculations were performed to assess the binding affinity and stability of the ligand-PARP1 complexes (PDB ID: 5DS3). Interaction analyses focused on hydrogen bonding and key amino acid residues. ADME (Absorption, Distribution, Metabolism, and Excretion) profiling was conducted to evaluate pharmacokinetic properties and drug-likeness. Results: Compound 6 (chloro phenyl acetamide) exhibited the highest docking score (-7.19 kcal/mol) and binding free energy (-67.26 kcal/mol), outperforming Olaparib (-7.06, -61.12 kcal/mol) and Niraparib (-6.99, -60.42 kcal/mol). Hydrogen bonding and π–π stacking interactions with critical residues such as GLY863 and TYR907 reinforced strong and stable binding. ADME results indicated low CNS penetration, high intestinal absorption, and minimal cardiotoxicity risk across all compounds, with most satisfying Lipinski’s Rule of Five. Conclusion: The study identified compound 6(chloro phenyl acetamide) as the most promising PARP1 inhibitor, with superior binding affinity, thermodynamic stability, and favorable pharmacokinetic properties. These findings support its potential as a lead compound for further experimental validation in cancer therapy..